Selective Patterning of Gold Surfaces by Core/Shell, Semisoft Hybrid Nanoparticles - Moraes, John; Ohno, Kohji; Maschmeyer, Thomas; Perrier, Sébastien (Small, 2015)
The generation of patterned surfaces with well‐defined nano‐ and microdomains is demonstrated by attaching core/shell, semisoft nanoparticles with narrow size distribution to microdomains of a gold‐coated silicon wafer. Near monodisperse nanoparticles are prepared using reversible addition‐fragmentation chain transfer (RAFT) polymerization, initiated from a silica surface, to prepare a polystyrene shell around a silica core. The particles are then used as‐prepared, or after aminolysis of the terminal thiocarbonyl group of the polystyrene shell, to give thiol‐terminated nanoparticles. When gold‐coated silicon wafers are immersed into very dilute suspensions of these particles (as low as 0.004 wt%), both types of particles are shown to adhere to the gold domains. The thiolated particles adhere selectively to the gold microdomains, allowing for microdomain patterning, while particles that contain the trithiocarbonate functionality lead to a much more even coverage of the gold surface with fewer particle aggregations. The preparation of monodisperse particles with a silica core and a polystyrene shell is described using reversible addition‐fragmentation chain transfer (RAFT) polymerization. The particles prepared this way display either trithiocarbonate or thiolate end groups. The thiolated particles are shown to selectively deposit onto gold domains of a patterned silicon wafer while trithiocarbonate‐functionalize particles deposited onto both gold and silicon domains with an aggregation‐free coverage.